Early treatment revisions by addition or switch for type 2 diabetes: impact on glycemic control, diabetic complications, and healthcare costs. Issue 1 (18th February 2016) - Schwab, Phil; Saundankar, Vishal; Bouchard, Jonathan; Wintfeld, Neil; Suehs, Brandon; Moretz, Chad; Allen, Elsie; DeLuzio, Antonio
Abstract : Background: The study examined the prevalence of early treatment revisions after glycosylated hemoglobin (HbA1c) ≥9.0% (75 mmol/mol) and estimated the impact of early treatment revisions on glycemic control, diabetic complications, and costs. Research design and methods: A retrospective cohort study of administrative claims data of plan members with type 2 diabetes and HbA1c ≥9.0% (75 mmol/mol) was completed. Treatment revision was identified as treatment addition or switch. Glycemic control was measured as HbA1c during 6–12 months following the first qualifying HbA1c ≥9.0% (75 mmol/mol) laboratory result. Complications severity (via Diabetes Complication Severity Index (DCSI)) and costs were measured after 12, 24, and 36 months. Unadjusted comparisons and multivariable models were used to examine the relationship between early treatment revision (within 90 days of HbA1c) and outcomes after controlling for potentially confounding factors measured during a 12-month baseline period. Results: 8463 participants were included with a mean baseline HbA1c of 10.2% (75 mmol/mol). Early treatment revision was associated with greater reduction in HbA1c at 6–12 months (−2.10% vs −1.87%; p<0.001). No significant relationship was observed between early treatment revision and DCSI at 12, 24, or 36 months (p=0.931, p=0.332, and p=0.418). Total costs, medical costs, and pharmacy costs at 12, 24, or 36 months were greater for the early treatment revision group compared with the delayed treatment revision group (all p<0.05). Conclusions: The findings suggest that in patients with type 2 diabetes mellitus, treatment revision within 90 days of finding an HbA1c ≥9.0% is associated with a greater level of near-term glycemic control and higher cost. The impact on end points such as diabetic complications may not be realized over relatively short time frames.